First-line Treatment Selection for Advanced Unresectable Biliary Tract Cancer (Canadian Oncology Today, 2025)
Biliary tract cancer (BTC) comprises a group of heterogenous malignancies that arise from the bile ducts (intrahepatic cholangiocarcinoma, extrahepatic cholangiocarcinoma) and the gallbladder (gallbladder cancer). Collectively, these malignancies carry a poor prognosis, which is attributed to the advanced stage at presentation. Historically, advanced BTC had a reputation of being less responsive to chemotherapy, a theory that was changed in the last decade, likely due to improved biliary drainage techniques that consequently improve liver function. Few advances have been made in the treatment of advanced and unresectable BTC in the past couple of years.